A comparison between cryptography libraries used in BRSKI protocol for constrained devices - Ehlert, Ricardo R.; Soares, Laura R.; Nobre, Jéferson C. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
The lack of a standard protocol for bootstrapping constrained devices is still a challenge in the management of Internet of Things (IoT) and Healthcare Internet of Things (HIoT). The Bootstrapping Remote Secure Key Infrastructure (BRSKI) protocol is a standard proposed by the Internet Engineering Task Force (IETF) for non-constrained devices, with cBRSKI as a constrained variant. In this work we review the current state of authentication protocols for constrained environments, emphasizing use-cases in the healthcare scenario. Then, we compare the memory usage and execution time of the cryptography library used in the reference implementation of both BRSKI and cBRSKI with lightweight alternatives. A test implementation was written using WolfSSL to perform the Cryptographic Message Syntax (CMS) signing function of the protocol, which is performed by OpenSSL in the reference implementation. Our experiments show that the lightweight library results in reduced bootstrap time and memory usage, without harming functionality. These findings highlight alternative BRSKI implementations suitable for constrained devices, and demonstrate that using lightweight cryptography libraries is recommended for IoT and HIoT.